Peluang dan Tatangan Dinas Pariwisata Dairi Membangun TWI Menjadi Wisata Religius - Indra Harahap; Rizki Fachru Rahman (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
The development of a tourist destination area is one thing that must always be considered and implemented, because the development of a tourist destination area determines what the future of the tourist destination area will be like. Taman Wisata Iman is a potential tourist destination that needs to be developed. This is because the features of the religious tourism park itself are very different from pine forests in general. The presence of houses of worship for five religions in Indonesia makes this religious tourism park a place of worship or a resting place for tourists. Each building in Taman Wisata Iman has its own meaning. For example, in Islam, residents are given a replica of the Kaaba for pilgrimage rituals. The large statue of Adam and Eve celebrates the beginning of human life on earth. Apart from worship at the Usko tourist park, visitors can enjoy camping, outdoor activities, children's playgrounds and shopping for souvenirs at the Usko tourist park. Usko tourism park also often organizes events to support tourism development, such as charity events for park maintenance in pine forests, scout weekend camps and many more. The purpose of this study is to analyze and become material that supports the development of attractions at Taman Wisata Iman Sitinjo. In this study the implementation activities and the impact of the implementation are described in a narrative manner using qualitative methods. Data collection techniques with observation, interviews and documentation. Methods of data analysis with data reduction, presentation and triangulation. The results of the study show that the role of the community and government in the development of the Sitinjo Iman Tourism Park as a tourist destination is very impressive. This was revealed through interviews with managers and employees of the Dair Regency Tourism Office. Year after year, this relatively minimal development repeatedly makes visitors bored and don't want to visit. The number of support services that are not paid attention to also makes visitors rate Taman Wisata Iman reviews on websites and personal blogs as lacking, which leads to a decrease in tourist interest. In the future, the authors hope that the management and government will pay more attention to the Iman Tourism Park tourist attraction by adding other tourist objects so that tourists don't get bored easily, and also pay attention to support services so that they can be repaired or improved immediately. Keywords: opportunities, challenges, faith tourism park,